Hexavalent chromium and stomach cancer: a systematic review and meta-analysis. (7th February 2019) - Suh, Mina; Wikoff, Daniele; Lipworth, Loren; Goodman, Michael; Fitch, Seneca; Mittal, Liz; Ring, Caroline; Proctor, Deborah
Abstract: Hexavalent chromium [Cr(VI)] is known to cause lung cancer in workers of certain industries, but an association with stomach cancer is uncertain and widely debated. Systematic review and meta-analyses were conducted to assess the risk of stomach cancer mortality/morbidity in humans and experimental animals exposed to Cr(VI). In accordance with the protocol (PROSPERO #CRD4201605162), searches in PubMed and Embase ®, and reviews of secondary literature bibliographies, were used to identify eligible studies. Critical appraisal of internal validity and qualitative integration were carried out using the National Toxicology Program's Office of Health Assessment and Translation (OHAT) approach; meta-analyses were conducted based on the occupational data (the only data suitable for quantitative assessment). Forty-seven publications (3 animal, 44 occupational, 0 non-occupational) met the eligibility criteria. Stomach cancer was only observed in one high risk of bias animal study, and in the low risk of bias studies no stomach cancer was observed. Thus, confidence in this evidence base is high. Environmental epidemiology studies did not meet eligibility criteria because exposure and outcome were not measured at the individual level. Meta-analyses of human data resulted in overall meta relative risks of 1.08 (95% CI: 0.96–1.21) including all studies and 1.03 (95%CI: 0.84–1.26) excluding studies associated with the highest risk of bias. Because most occupational studies have high risk of bias for confounding and exposure domains, the overall confidence in this evidence base is low to moderate. Combining the streams of evidence per the OHAT approach, Cr(VI) does not pose a stomach cancer hazard in humans.